Students’ Experiences, Engagement, and Attitudes in the English Education Revolution: The Role of Interactive Technology - Mahdi, Mohammed Abbas; Dewi, Desi Surlitasari (International Journal of Educational Qualitative Quantitative Research, 2025)
The digital revolution in education has fundamentally transformed English language learning by promoting a more interactive, flexible, and student-centered approach. In this context, students’ experiences, engagement, and attitudes toward interactive technology have become crucial for understanding the direction of English education in the modern era. This study aims to explore how students’ learning experiences and engagement in technology-based environments influence their attitudes toward the revolution in English education. Using a quantitative approach with multiple linear regression analysis, data were collected through a closed-ended questionnaire. A total of 200 English learners from Iraq and Indonesia participated in the study through online data collection. The findings confirmed that the English language education revolution through interactive technology has a positive and significant effect on students’ learning experience, engagement, and attitudes. Additionally, the revolution in interactive education technology was found to simultaneously and significantly affect all three dimensions. Students generally expressed strong support for the transition from traditional methods to more digital, collaborative, and personalized learning environments. Active engagement in interactive platforms contributed to more favorable attitudes toward the educational innovation. These results affirm that interactive technology serves not merely as a support tool, but as a driving force in shaping a sustainable and adaptive learning ecosystem. This study contributes to the fields of English language teaching and educational technology by emphasizing that digital strategies must enhance learning experiences, foster student engagement, and nurture positive learner attitudes in order to meet the needs of 21st-century education.